Oblongionosides A-F, megastigmane glycosides from the leaves of Croton oblongifolius Roxburgh - Yuya Takeshige (2018)
From the 1-BuOH-soluble fraction of a MeOH extract of the leaves of Croton oblongifolius Roxburgh, collected in Chiang Mai, Thailand, six megastigmane glycosides, named oblongionosides A-F were isolated together with eight known compounds, and their structures elucidated on the basis of spectroscopic data. Absolute structures were determined by HPLC analyses and application of the modified Mosher's method. © 2012 Elsevier Ltd. All rights reserved.